Evaluation Of Analgesic Activity Of Clerodendrum Viscosum Linn. (Verbenaceae) Leaves On Experimental Animal Model - DAS J.K; KANDAR C. C; DEY S.P; MANDAL S.C (International Journal of Pharma and Bio Sciences, 2011)
The main objective of the present investigation is to evaluate the analgesic activity of ethanolic extract of leaves of Clerodendrum viscosum (EELCV) on rats. Analgesic activity of EELCV at a dose of 100, 300 and 1000mg/kg and 500mg/kg & 2.5 mg/kg of pethidine was evaluated against the standard drug pethidine at a dose of 5mg/kg. Adult Swiss albino rats of either sex of six numbers in each group was undertaken for study and evaluated by tail flick method (for central action). The analgesic activity profile of ethanolic extract at different doses of 100, 300, 1000mg/kg and combination of 500mg/kg extract and 2.5 mg/kg of pethidine showed significant (p<0.05 & p<0.01) analgesic activity when compared with control and pethidine treated animals. Thus, ethanolic extract of leaves of Clerodendrum viscosum exhibited marked central analgesic effect in dose dependent manner